LANGUAGE ATTITUDE TOWARD ENGLISH AMONG ENGLISH LECTURERS FROM CENTRAL JAVA IN UNIVERSITAS PAMULANG - Taman, Purwanti; Retnawati, Saptina (ICoLLiTec (International Conference on Literature Linguistics and Teaching), 2023)
This study intended to describe the language attitude toward English among English Lecturers from Central Java in Universitas Pamulang. A qualitative method was applied, and the data were gathered through interviews and observation. There are five English lecturers from Central Java involved in this study as participants. The data were analyzed based on characteristics of language attitude: loyalty, pride, and awareness of the norm. The result of the analysis revealed that all participants have positive language attitudes toward English as they fulfill all positive language attitude characteristics. They tend to be loyal in using English in different levels of situations. They also feel proud of using English in all domains, especially in the social domain. Moreover, they are aware of the norms for using English in daily life correctly and politely